Molecular Modification and Enzymatic Properties of the Novel α-Glucosidase Aga432 - Han LU; Ting FANG; Xiaoxu NIU; Xiaomin WENG; Fen YAN (Shipin gongye ke-ji)
This study aimed to clone the novel α-glucosidase gene Aga432 from Paenibacillus sp. and enhance its catalytic activity through site-directed mutagenesis. A gene fragment encoding α-glucosidase was successfully amplified from the genomic DNA of Paenibacillus sp., comprehensive sequence analysis was performed, and homology modeling and molecular docking were employed to construct gene-engineered strains. Eight positive mutant strains were identified, among which the enzymatic properties of recombinant Aga432 and the highest relative activity mutant AT-2 were characterized. Additionally, the dispersing effects of recombinant α-glucosidases Aga432 and AT-2 on biofilms were explored, and their toxicity to mouse embryo fibroblasts was evaluated. The results revealed that the specific activity of Aga432 was 45.05 U/mg, while the mutant AT-2 exhibited a significantly enhanced specific activity of 84.09 U/mg. Although the optimal reaction temperature and pH for AT-2 were essentially unaltered relative to Aga432, its thermal stability was significantly enhanced, and it exhibited heightened stability under acidic conditions. The Km of mutant AT-2 was 2.18 times that of Aga432, the Vmax was 3.19 times, the Kcat was 2.33 times, and the Kcat/Km was 1.07 times that of Aga432. In vitro cellular assays indicated that Aga432 and AT-2 at concentrations of 15.0~30.0 μg/mL were non-toxic and exhibited good cell compatibility. Biofilm dispersal assays demonstrated that both recombinant α-glucosidases at concentrations ranging from 10.0 to 50.0 μg/mL significantly dispersed bacterial biofilms (P<0.0001). The thermostability of α-glucosidase Aga432 was successfully enhanced through molecular modification in this study, laying a foundation for the development of novel α-glucosidases and providing a reference for future targeted modification research.